Updated Hemodynamic Definition and Classification of Pulmonary Hypertension - Lechartier, Benoit; Kularatne, Mithum; Jaïs, Xavier; Humbert, Marc; Montani, David (Seminars in Respiratory and Critical Care Medicine, 2023)
Pulmonary hypertension (PH) is a pathophysiological manifestation of a heterogeneous group of diseases characterized by abnormally elevated pulmonary arterial pressures diagnosed on right heart catheterization. The 2022 European Society of Cardiology (ESC) and European Respiratory Society (ERS) Guidelines for the diagnosis and treatment of PH provides a new hemodynamic definition to define PH by lowering the threshold of the mean pulmonary artery pressure (mPAP) to 20 mm Hg. Precapillary PH is thus now defined as a mPAP >20 mm Hg together with a normal pulmonary artery wedge pressure (<15 mm Hg) and an increased pulmonary vascular resistance (>2 Wood Units). The ESC/ERS 2022 Guidelines also introduce a revised clinical classification of PH while retaining its previous distinction between the five groups according to the underlying pathophysiology.
Keywords: pulmonary hypertension; definition; classification